HUBUNGAN COLLEGE ENGAGEMENT DENGAN PRESTASI AKADEMIK MAHASISWA MUSLIM DI BANDUNG - Yuli Aslamawati; Enoch Enoch; Agus Halimi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
In regard to scientific journals that based on the empirical studies has shown that the advancement of education in Indonesia is hampered that characterized by the low of students’ mastery in science and technology. It happened because of the low student engagement in learning activities (college engagement). Therefore, it needs to examine relationship between college engagement with academic achievement (GPA) as a reflection of the mastery of learning subject. The respondent were determined based on the quality GPA through proportionate stratified random sampling technique that gained as much as 317 students, from several departments in UIN SGD and UNISBA. The design used correlational research, where college engagement variable measured by Engaged Learning Index (ELI). Statistical test used rank Spearman correlation test. The result has show a high correlation between college engagement and GPA (0.866), and student participation in the learning process was the highest dimension (0.846) associated with GPA